Contemporary hakka language maintenance in multilingual penang, malaysia - Wai See Ong, Teresa (Revista Linguagem & Ensino, 2020)
Malaysia is a multilingual country with 146 languages widely spoken. Among the Chinese community, which is the second largest ethnic group in Malaysia, Mandarin Chinese has become the mother tongue in recent years as many claimed it represents their Chinese identity. Additionally, the influence of mass media and the use of Mandarin Chinese as the main medium of instruction in Chinese-medium primary schools have motivated parents to shift from speaking Chinese heritage languages to Mandarin Chinese to their children at home. This shift has caused sociolinguistic realignment within many Chinese families in Malaysia and, ultimately, erased various language backgrounds. Like other Chinese heritage languages in Malaysia, Hakka currently faces many challenges in terms of language maintenance. To ensure its survival in Malaysia, it is vital to examine the current linguistic situation of Hakka. Addressing this gap, this study examines language practices, ideology, and community-based initiatives to maintain Hakka in Penang and provides new insights into the process and prospects for language maintenance.